A novel model for retinal imaging in the diagnosis of Alzheimer’s disease - Kimia Heydari; Elizabeth J. Enichen; Serena Wang; Grace C. Nickel; Joseph C. Kvedar (npj Digital Medicine)
Alzheimer’s disease is the fifth-leading cause of death for adults over the age of 65. Retinal imaging has emerged to find more accurate diagnostic tool for Alzheimer’s Disease. This paper highlights Hao et al.’s development of a new deep learning tool, EyeAD, which studies Optical Coherence Tomography Angiography (OCT-A) of patients with Alzheimer’s. Integrating this model into clinical workflows may offer novel insights into the progression of this disease.